How tall, how short, how faraway - Adler, David A.; Tobin, Nancy (New York : Holiday House, 1999)
Introduces several measuring systems such as the Egyptian system, the inch-pound system, and the metric system.
Book Links (A.L.A.).
School Library Journal.
Wilson's Children.
4.2
K-3
Keywords: Measurement -- Juvenile literature; Measurement; Measurement